Biolift four points technique: new horizons for the administration of cross-linked fillers at three different molecular weights - Cerutti, Luisa; Stripoli , Tania (Aesthetic Medicine, 2023)
Hyaluronic acid is one of the main constituents of injectable fillers, medical devices widely used in aesthetic medicine to prevent or treat skin aging. Fillers differ in rheological and physico-chemical properties derived from their production process such as molecular weight, concentration of hyaluronic acid, mechanism and degree of cross-linking. Zhoabex Soft Touch Filler is a hyaluronic acid formulation with three molecular weights and can be used in the minimally invasive approach named Biolift Four Points technique. The Biolift Four Points technique arises from the analysis and comparison of different techniques and it consists in identifying four specific anatomical points of the face for a functional and effective administration. The administration of Soft Touch with the minimally invasive Biolift Four Points technique improves hydration and texture with an appreciable lifting effect.